MODELLING THE EMPLACEMENT OF COMPOUND LAVA FLOWS - Blake S.; Bruno B.C. (My University, 2000)
The physical variables controlling crust-dominated lava flow have been investigated using laboratory experiments in which molten polyglycol wax was extruded from a point source on to a horizontal plane under cold water. The wax initially spread axisymmetrically and a crust of solid wax grew. Eventually wax broke out from the flow's periphery, sending out a flow lobe which in turn cooled and produced another breakout. The process repeated itself many times, building a 'compound lava'. The time for the first breakout to form correlates well with the theoretically predicted time (tc) required for cooling to form a crust thick enough for its strength to limit the flow's spreading rate. This time is proportional to the product of effusion rate (Q) and initial magma viscosity (μ) and inversely proportional to the square of the crust strength at the flow front. The number of flow units and the apparent fractal dimension of the flow perimeter increase with time normalised by tc. Our model illuminates the physical basis for the observation by Walker [G.P.L. Walker, Bull. Volcanol. 35 (1972) 579-590] that compound lava flows form by slow effusion of low viscosity magma, whereas faster effusion and higher viscosity favour lavas with fewer flow units. Because compound flows require t#tc, and given that tc#Qμ and the relationship between volume and effusion rate is V=Qt, simple and compound lava flows are predicted to fall in separate fields on a graph of μ against V/Q2, all else being equal. Compound flows plot at small values of μ and large values of V/Q2, with the position of the simple/compound boundary defined by field data implying a crust strength of order 104 Pa for basaltic to intermediate lavas. Whether a flow remains as a simple flow or matures into a compound flow field depends on the combined effect of viscosity, eruption rate and eruption duration (and hence volume) and these parameters need to be taken in to account when using morphology to infer eruption conditions. In particular, compound flows form from terrestrial subaerial point source eruptions on horizontal ground when μ<0.002V/Q2.
Keywords: LAVA; EMPLACEMENT; ERUPTIONS; MODELS; LABORATORY STUDIES